(untitled) - Food and Agriculture Organization of the United Nations (Rome, 2008)
This document details the methodology, the results of debates and the recommendations of the regional workshop on safety at sea in artisanal and small-scale fisheries in Latin America and the Caribbean. It also contains the presentations of the experts that participated in the workshop and the work plan required for the development of a regional strategy for safety at sea in small-scale fishieries
Keywords: Fishing boats,Tàu thuyền đánh cá; Safety measures,Biện pháp an toàn